Stress and Sleep Disorders in Polish Nursing Students During the SARS-CoV-2 Pandemic—Cross Sectional Study - Bodys-Cupak, Iwona; Czubek, Kamila; Grochowska, Aneta (Frontiers in Psychology, 2022)
Introduction The world pandemic of the virus SARS-CoV-2 , which causes COVID-19 infection was announced by the World Health Organization (WHO) on March 11, 2020. Due to the restrictions that were introduced in order to minimize the spread of the virus, people more often suffer from stress, depression, anxiety, and sleep disorders. The aim of this study was evaluation of the stress levels and sleep disorders among nursing students during the pandemic SARS-CoV-2 . Materials and Study Methods This is a cross-sectional study conducted among 397 nursing students on March 2020. The research tools used were original questionnaires, Perceived Stress Scale (PSS10), and the Athenian Insomnia Scale (AIS), as well as Coping with Stress Inventory (MiniCOPE). Results Respondents felt a high level of stress, which occurred in 68.8% of interviewees regarding whether there was a danger of contracting COVID-19. Respondents experienced 84% stress levels when a family member suffered from COVID-19. Sleep disorders were determined mainly by the fear of infection and contact with someone who might be infected with the virus. Nursing students who felt a high level of stress often suffered from sleep disorders (70.2%) more frequently than students who felt a low or average stress level (30.4%). The respondents decided to cope with stress by denial, taking psychoactive substances, ceasing action, or blaming themselves. The greater the intensity of stress experienced by students, the more often they undertook avoidance behaviors or showed helplessness. Conclusion During the pandemic, students experienced severe stress, which resulted in sleep disorders and avoidance behaviors.